PENGARUH PENGUNGKAPAN ASPEK EKONOMI DAN STRUKTUR MODAL TERHADAP KINERJA PERUSAHAAN (Studi Pada Perusahaan Pertambangan dan Manufaktur yang Terdaftar di BEI Tahun 2015-2016) - ALYSSA ALMAS SHADRINA (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
The purpose of this research is to examine the effect of economic aspect disclosure and capital structure on company performance. Economic aspect disclosure is measured using Sustainability Report Disclosure Index (SRDI) and capital structure is measured using Debt to Asset Ratio (DAR). Company performance is measured using Return On Asset (ROA), and firm size is used as the control variable. The population of this research is companies listed in the Indonesia Stock Exchange (IDX) in the period of 2015-2016. Using purposive sampling method, 21 companies are selected as the research sample. The result of multiple linear regression analysis show that economic aspect disclosure and capital structure have positive effects on company performance. Keywords: economic aspect disclosure, capital structure, company performance, firm size